Respuesta :

Answer:

this should help XD

Step-by-step explanation:

et's solve your equation step-by-step.

√2x−3+3=x

Step 1: Add -3 to both sides.

√2x−3+3+−3=x+−3

√2x−3=x−3

Step 2: Solve Square Root.

√2x−3=x−3

2x−3=(x−3)2(Square both sides)

2x−3=x2−6x+9

2x−3−(x2−6x+9)=x2−6x+9−(x2−6x+9)(Subtract x^2-6x+9 from both sides)

−x2+8x−12=0

(−x+2)(x−6)=0(Factor left side of equation)

−x+2=0 or x−6=0(Set factors equal to 0)

x=2 or x=6

Check answers. (Plug them in to make sure they work.)

x=2(Doesn't work in original equation)

x=6(Works in original equation)

If x=6, than the equation is $\sqrt{2(6)-3}+3=6.$ simplified this equals $\sqrt{12-3=9}+3=6$